Fenomena Kepercayaan Dan Amalan Masyarakat Dalam Perubatan Islam Di Malaysia - Ahmad Najaa' Mokhtar; Muhammad Khairi Mahyuddin; Abdul Rahim Zumrah; Rosidayu Sabran; Mohd Rumaizuddin Ghazali; Jahid Hj Sidek; Mahyuddin Ismail (Institut Agama Islam Al Mawaddah Warrahmah Kolaka, 2024)
Non-Indexed Publication